ANALISIS GAYA HIDUP SEHAT SISWA KELAS VIII DI SMP NEGERI 1 PANGKALAN KERINCI - Musar Pikah; Agus Sulastio; Ali Mandan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The problem in this study is that there are still many students who experience a healthy lifestyle in their daily life. Many students pay less attention to their healthy lifestyle and pay less attention to what they consume. The purpose of this study was to determine how the lifestyle of the students of SMP Negeri 1 Pangkalan Kerinci. The population in this study were 116 grade VIII SMP Negeri 1 Pangkalan Kerinci students. This research is a research with a quantitative approach. The instrument in this research is to use a questionnaire questionnaire. The results showed that (1) the type of food consumed with a percentage of 7.18%, (2) types of drinks consumed with a percentage of 5.47%, (3) eating according to schedule with a percentage of 5.99%, (4) bathing with a the percentage of 2.99%, (5) cleaning the mouth and teeth with a percentage of 6.08%, (6) clean and suitable clothes with a percentage of 3.56%, (7) roles in the residence with a percentage of 9.27% (8 ) health maintenance with a percentage of 6.00%, (9) disease prevention with a percentage of 6.12% (10) seeking treatment with a percentage of 5.32% (11) health recovery with a percentage of 3.08% (12) adequate rest time with the percentage of 2.68% (13) sleep disorders with a percentage of 4.83% (14) the intensity of exercise with a percentage of 4.35%.Key Words: Healthy Lifestyle